Letter: should we have to include baclofen in the GORD therapy armamentarium? authors' reply. Issue 8 (27th September 2022) - Raymenants, Karlien; Van den Bergh, Jolinde; Tack, Jan
Abstract : LINKED CONTENT This article is linked to Pauwels et al papers. To view these articles, visit https://doi.org/10.1111/apt.17068 and https://doi.org/10.1111/apt.17183